Quality of life of older gynecologic oncology patients at the initiation of chemotherapy - Anne Grethe Kleven; Christine Miaskowski; Ann Helen Torstveit; Christine Seel Ritchie; Marie Ellström Engh; Elin Andersen; Inger Utne (Wiley, 2023)
Abstract Aim To evaluate older gynecologic oncology patients' quality of life (QOL) at the initiation of chemotherapy and compare their QOL scores with a female age‐matched general population (GP) sample. Design Cross‐sectional. Methods Older (n = 122) gynecologic oncology patients completed the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (QLQ‐C30) that evaluates global health and five functional scales (range from 0 to 100). Differences in QOL scores between our sample and the GP were evaluated using one‐sample t‐tests and effect sizes were calculated using Cohen's d. Results Patients' mean age was 70.7 years (±6.6). Mean scores for the function scales ranged from 58.5 (±31.1) for role function to 86.1 (±17.0) for cognitive function. Compared to the GP, our sample reported significantly lower scores for global health status, social, role and physical functioning, and a significantly higher score for cognitive functioning. No differences were found in emotional functioning scores. Patient or Public Contribution No patient or public contribution.